2023
DOI: 10.1017/jfm.2023.454
|View full text |Cite
|
Sign up to set email alerts
|

Power-generation enhancements and upstream flow properties of turbines in unsteady inflow conditions

Abstract: Energy-harvesting systems in complex flow environments, such as floating offshore wind turbines, tidal turbines and ground-fixed turbines in axial gusts, encounter unsteady streamwise flow conditions that affect their power generation and structural loads. In some cases, enhancements in time-averaged power generation above the steady-flow operating point are observed. To characterize these dynamics, a nonlinear dynamical model for the rotation rate and power extraction of a periodically surging turbine is deri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 43 publications
1
3
0
Order By: Relevance
“…As seen, FT (r) and CT (r) are almost unaffected by the rotor motion, because the oscillatory motion is relatively small, which is consistent with the experiments with model wind turbine rotors (Fontanella et al 2022;Meng et al 2022a). From the theoretical aspect, recent studies of Wei & Dabiri (2023) and Heck, Johlas & Howland (2023) have established relations between the thrust force for wind turbines with surge motion velocity amplitudes and yaw angles. For example, Wei & Dabiri (2023) has shown that the time-averaged rotor thrust of a periodically surging wind turbine ( FT ) is related to that of a stationary wind turbine FT,0 as follows:…”
Section: Motion-to-forcing Modelsupporting
confidence: 81%
See 2 more Smart Citations
“…As seen, FT (r) and CT (r) are almost unaffected by the rotor motion, because the oscillatory motion is relatively small, which is consistent with the experiments with model wind turbine rotors (Fontanella et al 2022;Meng et al 2022a). From the theoretical aspect, recent studies of Wei & Dabiri (2023) and Heck, Johlas & Howland (2023) have established relations between the thrust force for wind turbines with surge motion velocity amplitudes and yaw angles. For example, Wei & Dabiri (2023) has shown that the time-averaged rotor thrust of a periodically surging wind turbine ( FT ) is related to that of a stationary wind turbine FT,0 as follows:…”
Section: Motion-to-forcing Modelsupporting
confidence: 81%
“…Nonlinear effects are not considered by the present model, but it is of interest to take them into account in future. In this regard, the M2F model should be modified to include the nonlinear rotor forcing due to large rotor motion, as shown recently by Heck et al (2023) and Wei & Dabiri (2023); the F2W model should also take into account the interaction between modes and the wake-response-induced modifications of the time-averaged wake and the eddy viscosity. This can be achieved via an iterative approach as demonstrated by Rosenberg & McKeon (2019) in turbulent channel flows.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While analytical models for the time response of the full turbine rotor have recently been derived and experimentally validated (e.g. Mancini et al, 2020;Wei and Dabiri, 2023), these have not yet been connected to unsteady aerodynamics at the blade-section level. In the case of blade sections undergoing dynamic stall in large-amplitude disturbances, the semi-empirical model of Leishman and Beddoes (1989) may be employed at a blade-section level.…”
Section: Transverse Gustmentioning
confidence: 99%